This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I think you should specify what is μ ( n ) . It is not that famous a function.
Log in to reply
@Kartik Sharma Can you post a non-English solution here haha! thanks
Possibly by Mellin transfrom or contour or Laplace or ...
Log in to reply
Give me some time. I am thinking over it as I essentially solved the English way(as Keshore did).
Log in to reply
@Kartik Sharma – I'm posting a pure IBP solution quite some time soon. Looking forward to your solution!
Log in to reply
@Pi Han Goh – Have a look at my comment on Keshore's solution. You might disagree.
Log in to reply
@Kartik Sharma – I always prefer to find the solution which requires the least prerequisites.
But I'm always interested to learn non-English solutions as well!
Wow great solution. I was thinking of Lambert Series but I got stuck!
Is this the only approach?
Log in to reply
I used lambert series. Let me show you how.
f ( x ) = k = 1 ∑ ∞ k μ ( k ) ln ( 1 − x k )
Take the derivative with respect to x and use lambert series to get:
f ′ ( x ) = − x 1 k = 1 ∑ ∞ 1 − x k μ ( k ) x k = − x 1 × x = − 1
Therefore f ( x ) = − x + c and we can find that c = 0 by evaluating at x = 0
I did part 1 the same way.
Log in to reply
Oh my god!!! Why did I fail to differentiate???!?!? Thank you!
Log in to reply
@Pi Han Goh – Anytime, I really like this method. It takes no effort at all.
Problem Loading...
Note Loading...
Set Loading...
So, this is our problem -
k = 1 ∑ ∞ k μ ( k ) ln ( 1 − x k )
− k = 1 ∑ ∞ k μ ( k ) m = 1 ∑ ∞ m x k m
We will just use Dirichlet Convolution or just transforming the sum to the variable k m = n ,
− n = 1 ∑ ∞ k ∣ n ∑ k μ ( k ) n x n
Now, we know that μ ( n ) is just the Mobius Function i.e. sum of primitive nth roots of unity. It is just
= 1 if n is a square-free positive integer with even prime factors
= − 1 if n is a square-free positive integer with odd prime factors
= 0 if it is a square number
Hence, the sum we have used is just
= 1 if n=1
= 0 if n>1
As a result,
− n = 1 ∑ ∞ k ∣ n ∑ k μ ( k ) n x n = − 1 x 1 + 0 = − x